Statistical Optimization of Tween-80-Assisted Potassium Hydroxide Pretreatment and Enzymatic Hydrolysis for Enhancing Sugar Yields from Corn Cob - Hui Zhang; Junhui Wu (Fermentation, 2023)
With the addition of Tween 80, potassium hydroxide pretreatment and enzymatic hydrolysis were statistically optimized to maximize sugar yields from corn cob (CC). The results indicated that the sugar yields from CC could be influenced significantly by the potassium hydroxide concentration, temperature and time during pretreatment. The optimized pretreatment conditions were as follows: potassium hydroxide, 46 g·L−1; Tween 80, 3.0 g·L−1; solid dose, 200 g·L−1; temperature, 78 °C; and time, 50 min. After optimization, the lignin reduction and recoveries of cellulose and hemicellulose were 89.7%, 97.8% and 68.0%, respectively. In addition, sugar production could also be influenced by the biomass loading, enzyme loading and reaction time. A maximal glucose production (518.48 mg·gds−1, milligrams per gram of dry substrate) and xylose production (351.14 mg·gds−1), 97.2% cellulose conversion and 82.9% hemicellulose conversion from CC could be obtained when the biomass loading was 195 g·L−1 and the enzyme loading was 8.9 FPU·gds−1 (filter paper activity units per gram of dry substrate) and when the Tween 80 concentration was 3.0 g·L−1 at 50 °C for 30.4 h during hydrolysis. This is the first systematic study of combined Tween 80 pretreatment of CC by potassium hydroxide and hydrolysis of CC by cellulase preparation to increase sugar production.